MANAJEMEN KURIKULUM TAHFIDZ PROGRAM AKSELERASI DAN RETENSI DALAM MENGHAFAL AL QUR’AN DI PONDOK HAMALATUL QUR’AN PUSAT JOGOROTO JOMBANG - Latief, Ma’mun Abdul; Solichin, Mujianto; Fanani, Achmad (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
This research aims to describe the management of the tahfidz curriculum for the acceleration and retention program for memorizing the Qur'an at the Hamalatul Qur'an Pondok Center in Jogoroto, Jombang. And This reasearch uses descriptive qualitative methods. The data collection techniques used interviews, documentation observation and triangulation. Analysis techniques include data collection, data condensation, data presentation and drawing conclusions. The results of this research indicate that the management of the tahfidz curriculum for the acceleration and retention program of Pondok Hamalatul Qur'an Center Jogoroto Jombang was carried out in several stages, namely, strategic planning, implementation of the daily activity schedule and evaluation of the activity program. The supporting factors for managing the tahfidz curriculum are getting full back up by caregivers, free education costs and a conducive environment. Meanwhile, the inhibiting factors are human resources who have not yet mastered management, infrastructure which is still inadequate and the ustadz's lack of knowledge in child psychology.